2015
DOI: 10.1631/jzus.b1400287
|View full text |Cite
|
Sign up to set email alerts
|

Numerical magnitude processing in abacus-trained children with superior mathematical ability: an EEG study

Abstract: Distance effect has been regarded as the best established marker of basic numerical magnitude processes and is related to individual mathematical abilities. A larger behavioral distance effect is suggested to be concomitant with lower mathematical achievement in children. However, the relationship between distance effect and superior mathematical abilities is unclear. One could get superior mathematical abilities by acquiring the skill of abacus-based mental calculation (AMC), which can be used to solve calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
0
4
0
1
Order By: Relevance
“…In most previous reports of MA expertise, students were self-selecting, highly motivated learners, who may have been especially predisposed to learning math in a visuo-spatial format (Frank & Barner, 2012;Hatano, Miyake, & Binks, 1977;Huang et al, 2015;Stigler, 1984;Stigler, Chalip, & Miller, 1986). Consequently, these studies left open the question of whether MA can be effectively implemented in the classroom environments that serve broader and more representative groups of elementary school children, where significant variability in visual Barner,Athanasopoulou,Chu et al 541 working memory abilities exist.…”
mentioning
confidence: 99%
“…In most previous reports of MA expertise, students were self-selecting, highly motivated learners, who may have been especially predisposed to learning math in a visuo-spatial format (Frank & Barner, 2012;Hatano, Miyake, & Binks, 1977;Huang et al, 2015;Stigler, 1984;Stigler, Chalip, & Miller, 1986). Consequently, these studies left open the question of whether MA can be effectively implemented in the classroom environments that serve broader and more representative groups of elementary school children, where significant variability in visual Barner,Athanasopoulou,Chu et al 541 working memory abilities exist.…”
mentioning
confidence: 99%
“…Pada Gambar 1 tersebut diketahui bahwa research berkaitan dengan abacus training, baru ditemukan 10 (sepuluh) dokumen yang relevan Zhang et al, 2023;Yujie et al, 2023;Mou et al, 2022;Nisha et al, 2021;Roy et al, 2020;Huang et al, 2015;Du et al, 2014;Li et al, 2013;Irwing et al, 2008;Hatta & Ikeda, 1988). Di Indonesia belum ditemukan research berkaitan dengan pelatihan keterampilan penggunaan abacus.…”
Section: Pendahuluanunclassified
“…Studies consistently show that children skilled in mental abacus have better arithmetic ability than those who did not receive mental abacus training (Amaiwa & Hatano, 1989;Barner et al, 2016;Chen et al, 2006;Donlan & Wu, 2017;Hanakawa, Honda, Okada, Fukuyama, & Shibasaki, 2003;Huang et al, 2015;Ku, Hong, Zhou, Bodner, & Zhou, 2012;Na, Lee, Park, Jung, & Ryu, 2015;Shen, 1999;Stigler, 1984;Wang et al, 2015;Wu et al, 2009). The arithmetic advantage from mental abacus training could be due to the implement of skilled mental abacus (e.g., Barner et al, 2016;Barner et al, 2018;Shen, 2006) or the familiarity of the numbers, arithmetic facts and procedures (e.g., Amaiwa & Hatano, 1989;Donlan & Wu, 2017;Rau, Xie, Li, & Chen, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…During training, learners should first transform the symbolic numbers (typically Arabic digits) into the non-symbolic number in physical abacus or mental abacus, then perform the computation following the rules of moving beads, and finally transform the non-symbolic number into symbolic number. Second, mental abacus training would result in better arithmetic performance (Amaiwa & Hatano, 1989;Barner et al, 2016;Chen et al, 2006;Donlan & Wu, 2017;Hanakawa, Honda, Okada, Fukuyama, & Shibasaki, 2003;Huang et al, 2015;Ku, Hong, Zhou, Bodner, & Zhou, 2012;Na, Lee, Park, Jung, & Ryu, 2015;Shen, 1999;Stigler, 1984;Wu et al, 2009), which typically has been shown to be associated with the non-symbolic number sense (e.g., Cui et al, 2019;Halberda et al, 2008;.…”
Section: Introductionmentioning
confidence: 99%